Correlation between Age and Defect Size with Increased Pulmonary Arterial Pressure in Adult Atrial Septal Defect (ASD) Patients at Cardiology and Vascular Medicine Department dr. Seotomo Public Hospital Surabaya 2019-2021 - Astrid Aulia Artiono Puteri; Yudi Her Oktaviono; Agung Prasmono (Cardiovascular and Cardiometabolic Journal, 2022)
Abstract: Atrial Septal Defect (ASD) is one of the three most common types of congenital heart disease in the world. Pulmonary arterial hypertension (PAH) is a complication that can be found in patients with secundum type of ASD. There is no research that shows the relationship between patient’s age and defect size with increased pulmonary artery pressure in secundum type of ASD patients in Indonesia, so further research needs to be done. Material and Methods: This study is a retrospective study using an observational analytical research design with cross sectionalapproach. The data from this study were taken from the medical records of ASD patients at the Cardiology and Vascular Department of Dr. Soetomo Public Hospital Surabaya. Results: Sex distribution of patients with secundum ASD was dominated by female patients with a total of 53 people (81.5%), the age distribution of patients was dominated by patients in the age group of 20-24 years as many as 18 people (27.7%). The most common comorbidities in adult secundum ASD patients were hypertension (3.08%) and minor CAD (3.08%). The mean diameter of the secundum ASD defect was 28.03±9.57 mm, and the data for the smallest defect diameter was 4 mm and the largest was 48 mm. Complications of increased PA pressure were dominated by 20 patients with mild PH (30.8%) and the mean mPAP pressure was 39.87±19.03. There were no patients with Eisenmenger syndrome Conclusion: There was no correlation between patient age and inter-atrial septal diameter with mPAP pressure. Keywords: Adult, mean Pulmonary Arterial Pressure (mPAP), pulmonary hypertension (PH), secundum Atrial Septal Defect (ASD)